What the citizen should know about our arms and weapons a guide to weapons from the 1940s - Hicks, James Ernest 1899- (Skyhorse Publishing, 2015)
Originally published in 1941, this book of military ordnance was written in order to bring information to the non-military public during the time of uncertainty that marked the beginnings of the United States' involvement in World War II. This volume was originally meant to bring comfort and understanding to the average citizen. Thorough in its scope, What the Citizen Should Know About Our Arms and Weapons covers such weapons as: * Pistols and revolvers * Muskets * Grenades and mortars * Field artillery * Antiaircraft artillery * And much more! Ideal for any military history buff, What the Citizen Should Know About Our Arms and Weapons is a straightforward look at the military practices of a nation on the brink of war. Skyhorse Publishing, as well as our Arcade imprint, are proud to publish a broad range of books for readers interested in history--books about World War II, the Third Reich, Hitler and his henchmen, the JFK assassination, conspiracies, the American Civil War, the American Revolution, gladiators, Vikings, ancient Rome, medieval times, the old West, and much more.